Boccaccio Between Naples and Florence, or the Desire to Become Two: Gendering the Author's Past in the Elegia di Madonna Fiammetta. (3rd April 2017) - Ronchetti, Alessia
Abstract: The history of the critical reception of the Elegia di Madonna Fiammetta (1343-44) exemplifies the various approaches that have characterized scholarly debates on Boccaccio's works. In the case of the Elegia, Boccaccio's decision to construct the authorial persona as a woman has led to contrasting, sometimes openly conflicting views regarding the true intentio this solution may have served. The credibility – the authority – of Fiammetta herself has often been particularly scrutinized. After a brief discussion of some reasons for this diversity of positions, this study proposes a new reading in which Fiammetta is considered one embodiment of a specific set of authorial stances, the other being Panfilo, the unfaithful lover. The dynamic interaction between these two gendered polarities can be better understood in relation to the topological structure underlying both the Elegia and Boccaccio's biography. This conceptual map revolves around two main centres: King Robert's Naples, where Boccaccio spent most of his youth; and Florence, his hometown, to which he had recently, and reluctantly, returned. The topological distinction between Naples and Florence is then associated with other distinctions present in the text: between past and present, between feminine and masculine, and between the two ethical and literary values of amore and pietà .